Antibacterial Activity of Ethyl Acetate Extract of Mango Bud (Mangifera indica L. var. Arum Manis) Against Multidrug-Resistant Bacteria - Mulangsri, Dewi Andini Kunti; Nisa, Maurizka Chairun; Sugihartanti, Diana Nuraini; Hidayah, Arini Ulfa (Universitas Muhammadiyah Surakarta, 2024)
Ethyl acetate extracts of Mangifera indica leaves had chemical constituents such as saponins, alkaloids, phenols, tannins, flavonoids and diterpenes. Purified extract of Mangifera indica leaves had antibacterial activity against S. aureus and E. coli. This research aimed to know the antibacterial activity of mango bud (Mangifera indica L. var Arum Manis) against S. aureus, E. coli, P. aeruginosa and their multidrug resistant spesies. Arum manis mango bud simplicia powder was extracted by maceration method used ethyl acetate solvent. This extract tested to flavonoids and alkaloids by qualitative methods. Antibacterial activity used disc diffusion method and the concentration of this extract such as 10, 20, 30, 40 and 50%. Data of antibacterial activity was analyzed by descriptively. Arum manis mango bud extract had antibacterial activity against all of tested bacteria with diameter of zone of inhibition at 6.76 – 12.20 mm. The arum manis mango bud extract contained flavonoids and alkaloids.